Analysis of Beta signal activity before and after smelling the scent of castor oil on Adolescent enthusiasm - Amirul Ma’arif; Aenul Mutmainah (Journal of Holistic Medical Technologies (JHMT), 2024)
Castor oil is an oil that Rasulloh favors. As in the Sahih Muslim Hadith, Rasulloh said, "the best fragrance is Castor oil," therefore this study aims to analyze the activity of beta signals in emotional adolescents. The research was conducted at the Modern Physics Laboratory of Universitas Islam Negeri Walisongo Semarang. This research is quantitative, with an experimental approach of as many as 20 respondents from the Faculty of Science and Technology of Universitas Islam Negeri Walisongo Semarang. Data were collected using the KT88 type EEG device for one minute without treatment and given the treatment of smelling the aroma of castor oil. In addition, respondents filled out an emotional intelligence questionnaire consisting of 5 questions with a scoring system using 3 Likert scales of normal, moderate, and high. Then, processing using Python software using the PSD (power spectral density) algorithm with the extraction method, in which the initial data is amplitude against time and then extracted into frequency against intensity. The results obtained in this study show that the frequency of beta waves before treatment and after treatment is 5.18% to 6.44%, respectively. The questionnaire score data before and after treatment is 7.75 to 9.15, respectively. It can be concluded that the aroma of Kasturi oil affects the increase in beta signals and enthusiasm of adolescents.